Constitutive models for rubber XII : proceedings of the 12th European Conference on Constitutive Models for Rubber (ECCMR 2022), September 7-9, 2022, Milano, Italy /: proceedings of the 12th European Conference on Constitutive Models for Rubber (ECCMR 2022), September 7-9, 2022, Milano, Italy. (2022) - Unknown
No abstract available